Raw data blood hematology fish from coastal lagoons - Carvalho, Luana (2025)
Raw data from blood samples of fish, Nile tilapia (Oreochromis niloticus) collected in coastal lagoons (Carapebus and Maembá) and in the aquaculture facility (Alegre) of the Espirito Santo State, Brazil, in March 2022.